Analisis Implementasi Kebijakan Pembebasan Bea Masuk Atas Impor Barang Untuk Keperluan Pelayanan Kesehatan Pada Masa Pandemi Covid-19 Di KPU Bea Dan Cukai Tipe A Tanjung Priok Tahun 2021 - Siska Adelia; Idar Rachmatulloh (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
The new variant of the Covid-19 virus has spread widely with a faster transmission process so that causes an increase in the number of Covid-19 virus infection cases. This dire situation eventually results in a shortage of procurement of imported health goods such as medical equipment, medicines and personal protective equipment (PPE) for the continuation of handling the Covid-19 pandemic. The purpose of this study was to analyze the implementation of the Import Duty Exemption Policy on the Import of Health Goods for the Purpose of Health Services during the Covid-19 Pandemic at the Prime Customs and Excise Office Type A Tanjung Priok in 2021. This study used a qualitative method with a descriptive approach. The results of the study explained that the implementation of the import duty exemption policy on imports of health goods received special attention related to the speed of handling, especially goods imported by government agencies for the purpose of handling the Covid-19 pandemic. The obstacles found were system errors so that the 2-hour service promise was not fulfilled, staff shortages during manual numbering services at the office, and obstacles from physical inspection of imported goods in the process of preparing containers and infrastructure for Temporary Place for Storage (TPS), including one of them is The number of load and unloading Workers (TKBM) that is not sufficient. For the efforts, i.e., system improvement by the Central IKC TIM, adding the number of employees for offline services, and conducting a physical inspection of imported goods in a coordination meeting held with the Temporary Place for Storage (TPS) party.